Politik Hukum Perburuhan Suatu Hasil Observasi terhadap Kebijakan dan Permasalahan Buruh Migran Indonesia - Johannes Pangehutan (Jurnal Hukum IUS QUIA IUSTUM, 2007)
Legal Politic in the Indonesian transision period is still inspired by some elements. Firstly, the political basis in Indonesia is elite politic. Secondly, political transision in Indonesian is still on the domination of the capital power. Thirdly, the transision process is pracmatic political process which indicates by the fighting of power among the  groups. Fourthly, the official governments who uphold the law has a srtategic  roles and functions to support the creation of national legal politic which craetes sosial  justice to Indonesian people.